2015
DOI: 10.4086/toc.2015.v011a003
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We identify a formal connection between physical problems related to the detection of separable (unentangled) quantum states and complexity classes in theoretical computer science. In particular, we show that to nearly every quantum interactive proof complexity class (including BQP, QMA, QMA(2), and QSZK), there corresponds a natural separability testing problem that is complete for that class. Of particular interest is the fact that the problem of determining whether an isometry can be made to produce a separ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…On the one hand, there are natural problems from quantum physics that are in QMA(2) but not obviously in QMA [21,22,39]. On the other hand, Harrow and Montanaro showed that, if the first equality in Eq.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, there are natural problems from quantum physics that are in QMA(2) but not obviously in QMA [21,22,39]. On the other hand, Harrow and Montanaro showed that, if the first equality in Eq.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
“…In recent years, there have been significant advances on the structure of quantum Merlin-Arthur systems, where multiple unentangled proofs and possibly locally restricted measurements in the verification were considered [10,16,[35][36][37]. It has been proven that many natural problems in quantum physics are characterized by quantum Merlin-Arthur proof systems (see, e.g., [21,22,38,39]). …”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
“…More recently Gutoski et al [85] generalized this work: for almost every complexity class defined by quantum interactive proofs, they give a version of the separability testing problem which is complete for that class. This shows that property testing problems can be used to characterize many quantum complexity classes.…”
Section: From Quantum Property Testers To Complexity Class Inclusionsmentioning
confidence: 99%
“…Since a failed SWAP test leads to the generation of a Bell pair, the CE also quantifies how well entanglement can be concentrated using two copies of the state and SWAP tests [28]. The controlled SWAP (cSWAP) used to measure CE is a basic building block in quantum communication protocols [29], and it has been recognized as an experimentally accessible tool for measuring and witnessing entanglement [28,30,31].…”
mentioning
confidence: 99%